Risks and Opportunities: REDD+, Biodiversity and People - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Robert Nasi, Director,CRP6, CGIAR Research Programme on Forests, Trees and Agroforestry, CIFOR talks about opportunities and risks "REDD+, Biodiversity and People". Video is made by Meerim Shakirova, social media reporter